Bridging Educational Traditions: A Comparative Study of Curriculum Reform in Southeast Asia and Europe - Ruslana Lyzhychko (PT. Islamic Research Publisher, 2024)
Curriculum reform has become a central agenda in global education systems as countries seek to balance tradition, innovation, and the demands of contemporary society. This study aims to analyze and compare the dynamics of curriculum reform in Southeast Asia and Europe, focusing on how educational traditions are integrated with modern pedagogical approaches. The research seeks to identify key similarities and differences in reform strategies, policy orientations, and implementation frameworks across both regions. This study employs a qualitative comparative research design using a systematic literature analysis and policy document review. Data were collected from academic publications, governmental curriculum frameworks, and international education reports related to curriculum reform in selected Southeast Asian and European countries. The data were analyzed through thematic comparative analysis to identify patterns of reform, institutional drivers, and contextual influences shaping curriculum transformation. The findings reveal that curriculum reform in Southeast Asia tends to emphasize cultural values, national identity, and competency-based learning aligned with socio-economic development goals. In contrast, European curriculum reforms focus more strongly on learner autonomy, interdisciplinary learning, and the integration of digital and critical thinking skills within broader frameworks of educational globalization. Despite these differences, both regions demonstrate a converging trend toward competency-based curricula, inclusive education, and the integration of 21st-century skills. The study also highlights that successful reform initiatives rely heavily on policy coherence, teacher capacity development, and adaptive governance mechanisms. This research contributes to the comparative education literature by providing a cross-regional analytical framework that bridges educational traditions with contemporary curriculum innovation. The study offers insights for policymakers and educators seeking to design contextually responsive curriculum reforms while maintaining global competitiveness and cultural relevance within evolving educational landscapes.